Circulating microRNA responses to acute whole-body vibration and resistance exercise in postmenopausal women - Buchanan, Samuel R.; Miller, Ryan M.; Nguyen, Michelle; Black, Christopher D.; Kellawan, J. Mikhail; Bemben, Michael G.; Bemben, Debra A. (Frontiers in Endocrinology, 2022)
Evaluating alterations in circulating microRNA (c-miRNA) expression may provide deeper insight into the role of exercise in the attenuation of the negative effects of aging on musculoskeletal health. Currently, there are sparse data on c-miRNA responses to acute exercise in postmenopausal women. The purpose of this study was to characterize the effects of acute bouts of resistance exercise and whole-body vibration on expression of selected c-miRNAs in postmenopausal women aged 65-76 years (n=10). We also examined relationships between c-miRNAs and muscle strength and bone characteristics. This randomized crossover design study compared c-miRNA responses to a bout of resistance exercise (RE) (3 sets 10 reps 70% 1 repetition maximum (1RM), 5 exercises) and a bout of whole-body vibration (WBV) (5 sets 1 min bouts 20Hz 3.38mm peak to peak displacement, Vibraflex vibration platform). DXA was used to measure body composition and areal bone mineral density (aBMD) of the total body, AP lumbar spine, and dual proximal femur. pQCT was used to measure tibia bone characteristics (4%, 38%, 66% sites). Blood samples were collected before exercise (Pre), immediately-post (IP), 60 minutes post (60P), 24 hours (24H), and 48 hours (48H) after exercise to measure serum miR-21-5p, -23a-3p, -133a-3p, -148a-3p (qPCR) and TRAP5b (ELISA). There was a significant modality × time interaction for c-miR-21-5p expression (p=0.019), which decreased from 60P to 24H after WBV only. TRAP5b serum concentrations significantly increased IP then decreased below Pre at 24H for both WBV and RE (p<0.01). Absolute changes in TRAP5b were negatively correlated with c-miR-21-5p fold changes (r= -0.642 to -0.724, p<0.05) for both exercise modalities. There were significant negative correlations between baseline c-miRNAs and bone status variables (r= -0.639 to -0.877, p<0.05). Our findings suggest that whole-body vibration is a sufficient mechanical stimulus for altering c-miR-21-5p expression, whereas a high intensity resistance exercise protocol did not elicit any c-miRNA responses in postmenopausal women. Increases in the bone resorption marker, TRAP5b, were associated with greater downregulation of c-miR-21-5p expression.